2021
DOI: 10.1021/acs.macromol.1c00386
|View full text |Cite
|
Sign up to set email alerts
|

Catechol as a Universal Linker for the Synthesis of Hybrid Polyfluorene/Nanoparticle Materials

Abstract: The attachment of conjugated polymers (CPs), characterized by their optical and electronic properties and excellent processability, to inorganic nanoparticles (NPs), known for their specialized electronic and photonic properties, has proven to result in unique and promising (hybrid) materials. Although CPs can be functionalized with many different end groups, the process to find a correct match between the desired NP and appropriate functional group on the CP is often tedious and time-consuming. This study aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In addition, the chain ends' functional groups offer the opportunity to mitigate their contribution as structural or electronic defects, 11 as well as to exploit suitable end groups to covalently assemble precise functional architectures. 12,13 For example, directional electron-transfer cascades can be readily achieved within redox-active block copolymer-based assemblies, 14 which inspired their iterative modular design. Notably, productive charge separation and transport vs unproductive recombination have gained recent attention, 15−17 exploiting the unraveled structure−property relationships to fine-tune the interplay of energy and electrontransfer steps.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the chain ends' functional groups offer the opportunity to mitigate their contribution as structural or electronic defects, 11 as well as to exploit suitable end groups to covalently assemble precise functional architectures. 12,13 For example, directional electron-transfer cascades can be readily achieved within redox-active block copolymer-based assemblies, 14 which inspired their iterative modular design. Notably, productive charge separation and transport vs unproductive recombination have gained recent attention, 15−17 exploiting the unraveled structure−property relationships to fine-tune the interplay of energy and electrontransfer steps.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The development of conjugated polymers enabled their broad application, e.g., in organic electronics, organic solar cells, organic light-emitting diodes, , or as sensors. , For these tasks, the photophysical and redox-chemical characteristics of such functional polymers are tailored by means of their repeating units, the degree of mutual electronic communication, and in the case of oligomers the precise number of these units. In addition, the chain ends’ functional groups offer the opportunity to mitigate their contribution as structural or electronic defects, as well as to exploit suitable end groups to covalently assemble precise functional architectures. , For example, directional electron-transfer cascades can be readily achieved within redox-active block copolymer-based assemblies, which inspired their iterative modular design. Notably, productive charge separation and transport vs unproductive recombination have gained recent attention, exploiting the unraveled structure–property relationships to fine-tune the interplay of energy and electron-transfer steps.…”
Section: Introductionmentioning
confidence: 99%
“…Among the reported semi-conducting polymers, polyfluorene is particularly interesting due to its excellent optical performance, easy synthetic accessibility and high stability. [9][10][11][12][13][14][15][16][17] Polyfluorene block copolymers are generally fabricated by grafting polyfluorene onto the chain end of another polymer or installing an active initiator onto the chain end of polyfluorene and then chain extending with a second monomer. However, these methods require tedious synthetic manipulation and are time consuming.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugated polymers exhibit excellent electrical and optical properties and have been extensively utilized in various applications, including light-emitting diodes, solar cells, biomedicines, etc. For the synthesis of conjugated polymers, the Pd(0)-catalyzed Suzuki cross-coupling polymerization reaction has proved to be a useful tool, affording various conjugated polymers in the previous decades. Hu et al reported that the preferential oxidation of renewable Pd(0) in the Pd(0) catalyst system during catalysis is important for realizing the transition from step-growth to chain-growth polymerization in Suzuki coupling reactions. Moreover, the Pd(0)/ t- Bu 3 P system has been identified as an effective catalyst for preferential oxidative addition. , Thus, this method has enabled the controlled preparation of π-conjugated polymers, e.g., polyfluorene (PF) and polythiophene, among which PF is particularly attractive for the preparation of functional copolymers owing to its excellent optical performance and conjugation ability. For example, Saito et al prepared several star-like copolymers bearing PF and polylactide arms and explored their self-assembly behavior. Mecking’s group designed and synthesized an amphiphilic copolymer comprising PF and poly­(ethylene glycol) blocks.…”
Section: Introductionmentioning
confidence: 99%